Administration of Immunomodulators to Treat Maternal and Fetal Infection Reduces Placental and Membrane Contamination - Royenko, A. A.; Pasieshvili, N. M. (Problems of Cryobiology and Cryomedicine, 2016)
Probl Cryobiol Cryomed 2016; 26(2):187.